Titik Temu Zuhud dan Kawruh Begja: Studi Komparatif Al-Ghazali dan Ki Ageng Suryomentaram - Panji Nur Muhammad Sholih; Fathur Rozi (JURNAL PUSAKA: Media Kajian dan Pemikiran Islam, 2025)
Amidst the wave of modernity characterized by the hegemony of materialism and technological disruption, modern humans face an acute existential crisis. The phenomena of alienation and spiritual emptiness have emerged as pervasive social pathologies. In Islam, Zuhud (asceticism/detachment) is proposed as a fundamental solution to overcome material dependency. However, the interpretation of Zuhud is frequently reduced to fatalism, structural poverty, and an anti-worldly stance, rendering it counterproductive to the spirit of contemporary progress. Conversely, the Nusantara archipelago possesses a repository of local wisdom known as Kawruh Jiwa or Kawruh Begja, initiated by Ki Ageng Suryomentaram, which offers a rationality of emotional processing. This study aims to conceptually reconstruct the meaning of Zuhud through the lens of Javanese indigenous psychology and to dissect the operational mechanism of "self-liberation" from Hubbud Dunya (love of the world) utilizing the analytical frameworks of Kramadangsa (ego-identity) and Mawas Diri (introspective self-awareness). This research employs a qualitative method with a library research design. Data analysis was conducted using a Gadamerian comparative-hermeneutic approach to establish a "fusion of horizons" between the classical Sufi texts of Al-Ghazali (11th Century) and the Javanese philosophical texts of Suryomentaram (20th Century), substantiated by contemporary research literature from 2021–2025. The findings indicate that Zuhud, as described in Minhajul ‘Abidin, shares an ontological correlation with the detachment of Sematan attributes in Kawruh Begja. The mechanism of Tazkiyatun Nafs (purification of the soul) demonstrates epistemological similarities with the Nyawang Karep (observing desires) technique, which functions as a form of Indigenous Mindfulness. Furthermore, the state of Nrimo (acceptance) is not characterized by passivity, but rather by emotional stability equivalent to Maqam Ridha. Kawruh Begja offers an operational articulation of Zuhud, rendering Islamic spirituality logically comprehensible as a form of ego management (Kramadangsa) aimed at achieving the "Liberated Human" (Manusia Tanpa Ciri). This synthesis is highly relevant as a foundation for mental health and a sustainable lifestyle in the modern era. Key words: Zuhud, Kawruh Jiwa, Kramadangsa, Mawas Diri, Islamic Psychology, Al-Ghazali, Ki Ageng Suryomentaram.